Pengaruh Tipe Industri, Growth, Profitabilitas, Dan Media Exposure Terhadap Carbon Emission Disclosure Perusahaan Industri High Profile Di Bursa Efek Indonesia - Bilbina, Arzet; Mubarok, Abdulloh; Raharjo, Teguh Budi (Jurnal Ekonomi Bisnis Digital, 2024)
Carbon emission disclosure refers to an important element of corporate social responsibility reporting that focuses on environmental issues. This information is usually included in additional reports published along with the Statement of Financial Accounting Standards (PSAK). This study aims to determine the effect of industry type, growth, profitability, and media exposure on carbon emission disclosure of high profile industrial companies on the Indonesian stock exchange. This research is a quantitative study with secondary data in the form of the company's annual financial statements. The sample of this study was selected using purposive sampling technique and obtained sample data as many as 21 companies with a total sample of 105 samples. The data analysis technique uses multiple linear regression analysis with the SPSS 22 program. The results of this study indicate that industry type and profitability have a positive effect on carbon emission disclosure. While growth and media exposure have no effect on carbon emission disclosure